ORGANIZING INDEPENDENT WORK OF STUDENTS IS THE KEY TO INCREASING THE QUALITY OF SPECIALIST TRAINING (Proceedings of International Educators Conference, 2023)
In this article, the author analyzes the role of students’ independent work in improving the professional quality of students in higher educational institutions. Information computer technologies and other software products can provide great assistance in organizing independent work, allowing you to significantly influence the design process, allowing you to simulate models of real processes, taking into account the probabilistic nature of the surrounding reality.